The effectiveness of a chemistry teaching module based on local wisdom of fermentation in enhancing students’ Higher Order Thinking Skills (HOTS) on acid base material - Turyani , Ima; Nevrita , Nevrita; Zaitun , Zaitun; Kurmalasari, Tety; Sukmawati , Wati (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The low level of students' higher-order thinking skills in chemistry learning, particularly acid-base material, indicates the need for innovative, contextual and meaningful teaching materials. This study aims to develop and test the effectiveness of a chemistry teaching module based on local fermentation wisdom in improving students' Higher-Order Thinking Skills (HOTS) in the implementation of the Independent Curriculum. The study used a Research and Development approach with a four-stage model, focusing on the development stage. The module's effectiveness was tested through a quasi-experimental design with a single pretest and posttest group involving eleventh-grade students. Data were collected using a HOTS test based on the local fermentation context and an observation sheet of learning implementation, then analyzed descriptively and inferentially. The results showed that the developed module was classified as very practical and easy to implement in learning. This module was also effective in improving students' HOTS, with the most prominent improvements in analytical and evaluation skills, as well as significant improvements in creative abilities. These findings indicate that the local fermentation wisdom-based module can be an alternative contextual teaching material to support students' HOTS development.